Pengaruh Iklim Komunikasi Organisasi Terhadap Kinerja Karyawan Matahari Mega Mall - Tambuwun, Andreas Moses; Sondakh, Mariam; Himpong, Meity D. (ACTA DIURNA KOMUNIKASI, 2018)
The purpose of this study was to find out how significant the influence of the climate of organizational communication on employee performance ofÂ  Matahari mega mall, there are six major factors of an Organizational Communication Climate in the form of Trust, Joint Decision Making, Honesty, Openness in downward communication, Listening in upward communication, Attention to high-performance goals, and six factors of Quality Performance, Quantity, Timeliness, Effectiveness, Need for Supervisory, Interpersonal Impact that can be used to measure this research. in this research using qualitative approach, survey method and correlation analysis and questionnaire as data collection tool, sempel technique using simple random sampling technique which is sampling technique of population member done randomly, with sample amounted to 50 Respondents.according to the results of data processing Hypothesis for significance test correlation found that there is a significant relationship between Climate Communications Organization with employee performance at Matahari Mega Mall Manado of 0.001. Keywords: Climate of Organization Communication, Employee Performance.